Louis-Alexandre Andrault, comte de Langeron, and Charles-Claude, marquis de Langeron, papers - Langeron, Louis-Alexandre Andrault, comte de, 1761-1831.; Langeron, Charles-Claude, marquis de, 1720-1792.
Correspondence, lists, rosters, charts, reports, embarkation orders and other material pertaining chiefly to French military and naval participation in the American Revolution. Includes lists of French fleets and regimental rosters of troops at Brest, France, 1776-1779; signals and rules for division of prizes in the French Navy; charts and reports on Louis Guillouet, m. le comte d' Orvillers' defeat of Admiral Viscount Augustus Keppel Keppel, 1778; intelligence reports on the British Navy, 1779; troop assignments for the French fleet, 1779; rosters of troops at St. Malo, France; a report on the siege of Savannah, Ga., 1779; and shipping lists, rosters, equipment lists, and embarkation orders for Jean-Baptiste-Donatien de Vimeur, comte de Rochambeau's army, and the supporting French fleet, 1780-1781.
French military officer.
Collection material in French.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Keppel, Augustus Keppel, -- Viscount, -- 1725-1786.; Orvilliers, -- M. le comte d' -- 1708-1792.; Rochambeau, Jean-Baptiste-Donatien de Vimeur, -- comte de, -- 1725-1807.; France. -- Armée -- History -- 18th century; France. -- Marine -- History -- 18th century; Great Britain. -- Royal Navy -- History -- 18th century; Brest (France) -- History, Military; France -- History, Military; France -- History, Naval; Saint-Malo (France) -- History, Military; Savannah (Ga.) -- History -- Siege, 1779.; United States -- History -- Revolution, 1775-1783 -- Participation, French; Army officers